Indigenous Cosmology of Kalimantan as an Alternative Theological Ecology - Arief Fahmi Lubis; Salman Imran; Gede Satya Wicaksana; Fatima Zahra; Zulkhaedir Abdussamad (Mahkota Science Publishers, 2026)
The indigenous cosmology of Kalimantan, Indonesia, can be understood as an ontological horizon that significantly contributes to reinterpreting the relationships among humankind, nature, and the transcendent dimension. This study aims to examine the indigenous cosmology of Kalimantan as a conceptual source for the development of an Islamic theological ecology that is more relational, contextual and sensitive to ecological justice. This study employs a qualitative approach, using a critical-hermeneutic ethnographic design, to interpret the ecological values, practices, and meanings embedded within indigenous cosmology, and to engage them in dialogue with the principles of tawḥīd, amānah, and balance in Islam. The findings indicate that the contemporary ecological crisis is not merely a matter of technical environmental management, but is also influenced by an anthropocentric worldview that separates humans from nature. In this context, Kalimantan’s indigenous cosmology offers a critical perspective on modern exploitative paradigms through its emphasis on relationship, responsibility, reciprocity and respect for nature. This study positions indigenous knowledge as a source of theoretical reflection rather than merely a cultural object, emphasising that its integration into Islamic theological discourse and environmental policy must be carried out with care to avoid reducing local meanings and to ensure that indigenous communities remain key actors.